2019
DOI: 10.1097/dcr.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

A Quality-of-Life Comparison of Two Fecal Incontinence Phenotypes: Isolated Fecal Incontinence Versus Concurrent Fecal Incontinence With Constipation

Abstract: BACKGROUND: Many patients with fecal incontinence report coexisting constipation. This subset of patients has not been well characterized or understood. OBJECTIVE: The purpose of this study was to report the frequency of fecal incontinence with concurrent constipation and to compare quality-of-life outcomes of patients with fecal incontinence with and without constipation. DESIGN: This was a prospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…Notably, a recent study in 946 patients referred for investigation of faecal incontinence showed that the majority also reported constipation symptoms (69¢3% c.f. 61¢4% in current study) [21]. The absence of awareness of this coexistence amongst referring clinicians was not evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 61%
“…Notably, a recent study in 946 patients referred for investigation of faecal incontinence showed that the majority also reported constipation symptoms (69¢3% c.f. 61¢4% in current study) [21]. The absence of awareness of this coexistence amongst referring clinicians was not evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 61%
“…Another recent study from the United States mirrors our findings, with 69.3% of 946 patients referred for investigation of faecal incontinence having underlying symptoms of constipation. 3 These results demonstrate that coexistent symptoms are very common though often missed.…”
mentioning
confidence: 82%
“…The impact of FI and CS on normal daily activity is considerable and involves all aspects of quality of life (QoL). The coexistence of FI and CS has been shown to affect both the psychological and physical domains as well as normal social activity; sexual activity is also affected by the presence of FI and CS [12][13][14]. The need to organize one's daily activities based on effective intestinal emptying or the risk of FI episodes and the psychological impact of embarrassing symptoms have a significant impact on QoL.…”
Section: Patients' Quality Of Lifementioning
confidence: 99%
“…In addition, Cauley et al demonstrated that patients with coexisting FI and CS have different clinical and anorectal physiology test findings and worse overall QoL [13]. These patients have a different clinical presentation characterized mainly by difficult bowel emptying and milder symptoms of FI.…”
Section: Patients' Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation